A high performance method for the accurate and precise determination of silicon isotopic compositions in bulk silicate rock samples using laser ablation MC-ICP-MS. Issue 9 (11th May 2020) - Zhang, Chenxi; Zhao, He; Zhang, Wen; Luo, Tao; Li, Ming; Zong, Keqing; Liu, Yongsheng; Hu, Zhaochu
Abstract : This study presents the most efficient silicon isotopic analysis method for bulk silicate rock samples by both nanosecond and femtosecond laser ablation MC-ICP-MS. Abstract : MC-ICP-MS has become one of the most powerful analytical methods for Si isotopes in bulk liquid and solid samples in the past decade. Laser ablation provides direct sampling of solid samples, avoiding laborious chemical digestion procedures. As for powder bulk samples, the preparation of stable and homogeneous targets prior to measurements, and strategies to minimize potential matrix effects, are critical for accurate isotopic analysis. In this study, an accurate and precise method for Si isotope ratio measurements by fs-LA-MC-ICP-MS of bulk silicate rock samples was established. A new laser fusion sample preparation technique was developed to achieve fast and homogeneous fusion of silicate rock powders (including granite and granodiorite that contain abundant refractory minerals) into glasses. Compared to the pressed pellet technique, the measurement precision for fused glasses was improved ∼5.7-fold. Matrix effects during Si isotopic analysis were observed when using non-matrix matched calibration protocols under normal dry-plasma instrument conditions with both ns- and fs-laser using a raster ablation mode. Matrix effects were eliminated by the addition of water vapor into the plasma, realizing accurate non-matrix matched calibration. In addition, using a fs-laser provided better measurement precision, with the internal and external precisions being improved ∼1.85 and ∼2.4 fold compared to a ns-laser at nearly equal signal intensities. Five well characterized silicate rock reference materials were analyzed using fs-LA-MC-ICP-MS calibrated against NBS-28 and BHVO-2G. Results obtained for δ 29 Si and δ 30 Si for these five reference materials were in agreement with previously reported values, confirming the accuracy of the proposed method.